Lithium spectral line formation in stellar atmospheres: the impact of convection and NLTE effects - Klevas, Jonas; Caffau, Elisabetta; Ludwig, Hans-Günter (Arxiv, 2015)
Different simplified approaches are used to account for the non-local thermodynamic equilibrium (NLTE) effects with 3D hydrodynamical model atmospheres. In certain cases, chemical abundances are derived in 1D NLTE and corrected for the 3D effects by adding 3D-1D LTE abundance corrections (3D+NLTE approach). Alternatively, average <3D> model atmospheres are sometimes used to substitute for the full 3D hydrodynamical models. We tested whether the results obtained using these simplified schemes (i.e., 3D+NLTE, <3D> NLTE) may reproduce those derived using the full 3D NLTE computations. The tests were made using 3D hydrodynamical CO5BOLD model atmospheres of the main sequence (MS), main sequence turn-off (TO), subgiant (SGB), and red giant branch (RGB) stars, all at [M/H]=0.0 and -2.0. Our goal was to investigate the role of 3D and NLTE effects on the formation of the 670.8 nm lithium line by assessing strengths of synthetic 670.8 nm line profiles, computed using 3D/1D NLTE/LTE approaches. Our results show that Li 670.8 nm line strengths obtained using different methodologies differ only slightly in most of the models at solar metallicity. However, the line strengths predicted with the 3D NLTE and 3D+NLTE approaches become significantly different at subsolar metallicities. At [M/H]=-2.0, this may lead to (3D NLTE)-(3D+NLTE) differences in the predicted lithium abundance of ~0.46 and ~0.31 dex in the TO and RGB stars, respectively. On the other hand, NLTE line strengths computed with the average <3D> and 1D model atmospheres are similar to those obtained with the full 3D NLTE approach for MS, TO, SGB, and RGB stars, at all metallicities; 3D-<3D> and 3D-1D differences in the predicted abundances are always less than ~0.04 dex and ~0.08 dex, respectively. However, neither of the simplified approaches can reliably substitute 3D NLTE spectral synthesis when precision is required.